PENGARUH DISIPLIN KERJA, MOTIVASI KERJA, ETOS KERJA DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN (LITERATURE REVIEW - Siti Putri Nur Syiva; Rizka Ayu Lestari; Eka Bagus Rahmad Lil'alamin; Riyan Sisiawan Putra (WORLDVIEW ( Development economic and sharia studies journal ), 2023)
Abstract This study aims to analyze the effect work discipline, work motivation, work ethic and work environment on employee work productivity. Work discipline is a workplace or management concept that demands regular behavior of employees. Work motivation is the encouragement or impetus for every employee to work carrying out his work. With good motivation, employees feet happy and enthusiastic about their work, which leads to significant development and growth in the organization. Work ethic is a value based on hard work and determination. Capitalists believe in the need for hard work and its ability to improve moral character. The work environment is everything that surrounds workers and can affect the performance of the tasks assigned to them, and labor productivity is the production capacity of workers compared to the inputs used. This type of research uses a literature review bye reviewing previous studies with analysis and drawing conclusions using references from national journals sources from Google Scholar. The results of this study indicate that work discipline, work motivation, work ethic, work environment affect employee work productivity.